Fixed Point and Convergence Results for Nonexpansive Set-Valued Mappings. (18th November 2021) - Reich, Simeon; Zaslavski, Alexander J.
Abstract: We present several fixed point and convergence results for nonexpansive set-valued mappings which map a closed subset of a complete metric space into the space.